Perlindungan Hukum terhadap Investor Perseroan Terbatas Akibat Pandemi Covid-19 - Rezeki, Abdus Salam; Prabowo, Agung Wira Hadi; Septian Samosir, Andi Kesuma; Hsb, Fiqria Muzdalifah; Hasril, Syafira; Anggraini, Fitri; Kumala, Sri Kumala; Siregar, Emiel Salim (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The Coronavirus Disease 2019 (COVID-19) pandemic has in fact provided impetus for a country to take 'abnormal' policies to break the chain of COVID-19, and Indonesia is no exception. the method of normative juridical approach, namely an approach to the problem by examining and reviewing an applicable and competent law and regulation to be used as a basis for carrying out problem solving. Legal protection is one of the elements to improve aspects of law enforcement in a country. Of course legal protection is given by the state to its people in order to create stability in any case, including in economic and legal matters. The principles adhered to in the Limited Liability Company itself, namely regarding the principles of good corporate governance. Presidential Regulation Number 44 of 2016 concerning List of Closed Business Fields and Open Business Fields with Requirements in the Investment Sector. Keywords: Covid-19, Legal Protection, Investors, Limited Liability Company